2016
DOI: 10.1589/jpts.28.2708-2712
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectrical impedance analysis for severe stroke patients with upper extremity hemiplegia

Abstract: [Purpose] This study is to analyze bioimpedance parameters and occupational assessment for severe stroke patients with upper extremity hemiplegia. [Subjects and Methods] Experimental subjects were 20 hemiplegic stroke patients receiving rehabilitation therapy between November to October, 2015. Prediction marker (PM), and phase angle (θ), a nd characteristic frequency (fc) were measured using bioelectrical impedance spectroscopy (MultiScan 5000). Bioelectrical impedance vector analysis (BIVA) was also obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
1
8
0
1
Order By: Relevance
“…However, these methods are quite subjective because it is difficult to obtain an accurate evaluation value and its test results also vary widely depending on the ability and skill of the examiner. According to our previous published paper, assessment of paretic and non-paretic regions of stroke subjects with upper extremity hemiplegia using bioelectrical impedance parameters agreed quite well with that using conventional assessment tools [36]. In addition, bioelectrical impedance parameters provide rehabilitation evaluator with the information about muscle strength and pathophysiological function for paretic and non-paretic regions of stroke hemiplegic patients.…”
Section: Bioelectrical Impedance Parameterssupporting
confidence: 60%
“…However, these methods are quite subjective because it is difficult to obtain an accurate evaluation value and its test results also vary widely depending on the ability and skill of the examiner. According to our previous published paper, assessment of paretic and non-paretic regions of stroke subjects with upper extremity hemiplegia using bioelectrical impedance parameters agreed quite well with that using conventional assessment tools [36]. In addition, bioelectrical impedance parameters provide rehabilitation evaluator with the information about muscle strength and pathophysiological function for paretic and non-paretic regions of stroke hemiplegic patients.…”
Section: Bioelectrical Impedance Parameterssupporting
confidence: 60%
“…Patients after stroke often require long-term rehabilitation therapy, especially for the hemiplegia in order to the restore and improve motor functions for the paralyzed limbs. [ 10 , 11 ] It has been reported that more than 50% patients can not recover arm function, although most stroke survivors can regain ability to walk independently after rehabilitation. [ 12 ] If arm function can not be recovered timely, this condition can also lead to secondary complications such as spasticity, contractures, and pain.…”
Section: Introductionmentioning
confidence: 99%
“…16 Several studies have shown a close association between BIA with cardiovascular and cerebrovascular events. 17,18 Among the most common fat indexes, including WC and waist-to-hip ratio, BIA has been shown to be better correlated with known serum adipocytokines and cardiometabolic risk markers. 19 In this context, it has been documented that BIA is closely associated with cardiometabolic risk and correlates better with cardiovascular events than waist circumference or body mass index alone.…”
Section: Discussionmentioning
confidence: 99%